The degree of inclusion of the dimensions of sustainable development in the book of computers and information technology for the second intermediate grade in the Kingdom of Saudi Arabia - Almohammadi, Ibtehal Abdulrahim; Saleh, Aeshah Mahmoud; Almohammadi, Najwa Atyan (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to determine the extent to which the dimension of sustainable development was included in second-grade secondary school computer and information technology books in Saudi Arabia. The study used the analytic, descriptive curriculum, and the researchers analyzed the computer and information technology book (Book of Chapter I and Book of Chapter II) scheduled for students of intermediate second grade, 1443 AH-2021, using the content analysis tool encompassing the social, economic, environmental and technological dimensions and concepts of sustainable development, and 37 concepts related to those dimensions; Results showed that the overall degree of inclusion of sustainable development dimensions in the Computer and Information Technology Book for the mid-second grade was low, and in percentage terms (25%), the results also showed an imbalance in the inclusion of sustainable development dimensions in the computer book and information technology, where the social dimension is including in the inclusion ratio (53.4%), and to an average degree, followed by the economic dimension, with an inclusion ratio (30%), and to a low degree, while the technological dimension received an inclusion ratio (12%), to a low degree, the environmental dimension came in the last order, a percentage (4.6%), and a low degree; The study recommended, inter alia, that the concepts of sustainable development should be appropriately and balanced in the content of the computer book and information technology for the second middle grade, that teachers should familiarize themselves with the dimensions and concepts of sustainable development, and that they should train students’ methods of development at different educational levels.